Research on the Central-Peripheral Interaction Mechanism of Taiji Standing Qigong - Qi, Liping; Tian, Zhihao; Yang, Shuye; Yang, Yulong; Liu, Liqing (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details